Dilemma of Dual Citizenship Issues in Indonesia: A Legal and Political Perspective (Universitas Negeri Semarang, 2022)
The issue of dual citizenships has been in much of the debate over the years. Many developed countries such as US, UK, Australia, and Switzerland have no restrictions on holding dual nationality, whereas countries such as Singapore, Austria, India, and Saudi Arabia do not “recognize” or “restrict” dual citizenships, leading to automatic loss of citizenship upon acquiring other. Some countries such as Austria, Spain may still grant dual citizenships upon certain special conditions under exceptional cases like celebrities. The implementation of dual citizenship nowadays is not something strange or unusual things internationally. By considering the international environment that is nowadays being wider and no limit, everyone has an easy access to go abroad. In Indonesia, the concept of dual citizenship still limited to the children from inter-marriage, while consider the amount of Indonesian diaspora in another country this is the time for Indonesia to upgrade or revise the citizenship system in Indonesia.